2002
DOI: 10.1007/s10006-002-0370-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospektive Phase-II-Studie zur neoadjuvanten Radiochemotherapie fortgeschrittener, operabler Mundhöhlenkarzinome

Abstract: Our present results demonstrated impressive clinical and pathological response rates of concurrent Taxol/carboplatin and radiotherapy as a preoperative treatment modality in advanced oral and oropharyngeal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Other outcome surveys of a similar therapeutic concept (preoperative RCT and radical surgery) reported about smaller cohorts and shorter periods of surveillance. Survival and control probability were found in a similar range with 2-year overall survival probabilities ranging from 63 to 86% and 2-year local control probabilities ranging from 68 to 84% 6,7,15,20 . Comparison with outcome data reported after postoperative adjuvant RCT is difficult.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Other outcome surveys of a similar therapeutic concept (preoperative RCT and radical surgery) reported about smaller cohorts and shorter periods of surveillance. Survival and control probability were found in a similar range with 2-year overall survival probabilities ranging from 63 to 86% and 2-year local control probabilities ranging from 68 to 84% 6,7,15,20 . Comparison with outcome data reported after postoperative adjuvant RCT is difficult.…”
Section: Discussionmentioning
confidence: 52%
“…It was shown that RT is likely to be more effective in otherwise unaffected and well oxygenated tissue 3,9,21 . The concept of administering RCT before surgery has been reported in studies by DOBROWSKY et al 6 , MOHR et al 20 , KIRITA et al 15 , and ECKARDT et al 7 . These authors report 2-year overall survival probabilities ranging from 63 to 86% and 2-year local control probabilities ranging from 68 to 84%.…”
mentioning
confidence: 94%
“…Of 20 patients included in this study (March 2004 - October 2006), 10 patients where treated without previous radiotherapy (group 1), five patients received conventional radiotherapy (59.4 - 72 Gy) (group 2) at least 22 months before surgery and another five patients received neoadjuvant chemoradiation 6 weeks before surgery (group 3, Table 1). The neoadjuvant chemoradiation protocol included cisplatin 12.5 mg/m 2 plus 40 Gy radiation or paclitaxel 40 mg/m 2 /carboplatin AUC 1.5 plus 40 Gy radiation [1,2]. During surgical procedure, 5-10 mm long vessel specimens where obtained by the surgeon.…”
Section: Methodsmentioning
confidence: 99%
“…The therapy of patients suffering from oral cancer could be recently improved by utilization of multimodal interdisciplinary regimes using a combination of surgery, chemo- and radiotherapy [1,2]. Extensive tissue defects following ablative tumor therapy do require adequate and functional reconstruction regardless of whether the patient received preoperative irradiation or not.…”
Section: Introductionmentioning
confidence: 99%
“…A potential outcome advantage for chemoradiotherapy in head and neck cancer has been further examined in several meta-analyses between 1990 and 2001 [3,18,19,20]. Its effectiveness concerning locoregional tumor control and recurrence-free survival was shown [6] previously, as well as a good activity of the combination with paclitaxel/carboplatin [11,21,22,23,24]. This high effectiveness was confirmed by the initially published 1- and 3-year results of the presented study where the overall survival rate after 3 years was 84% [25].…”
Section: Discussionmentioning
confidence: 99%